Latent Fairness in Adults’ Relationship-Based Moral Judgments - Hao, Jian; Liu, Yanchun; Li, Jiafeng (Frontiers in Psychology, 2015)
Can adults make fair moral judgments when individuals with whom they have different relationships are involved? The present study explored the fairness of adults’ relationship-based moral judgments in two respects by performing three experiments involving 999 participants. In Experiment 1, 65 adults were asked to decide whether to harm a specific person to save five strangers in the footbridge and trolley dilemmas in a within-subject design. The lone potential victim was a relative, a best friend, a person they disliked, a criminal or a stranger. Adults’ genetic relatedness to, familiarity with and affective relatedness to the lone potential victims varied. The results indicated that adults made different moral judgments involving the lone potential victims with whom they had different relationships. In Experiment 2, 306 adults responded to the footbridge and trolley dilemmas involving five types of lone potential victims in a within-subject design, and the extent to which they were familiar with and affectively related to the lone potential victim was measured. The results generally replicated those of Experiment 1. In addition, for close individuals, adults’ moral judgments were less deontological relative to their familiarity with or positive affect toward these individuals. For individuals they were not close to, adults made deontological choices to a larger extent relative to their unfamiliarity with or negative affect toward these individuals. Moreover, for familiar individuals, the extent to which adults made deontological moral judgments more closely approximated the extent to which they were familiar with the individual. The adults’ deontological moral judgments involving unfamiliar individuals more closely approximated their affective relatedness to the individuals. In Experiment 3, 628 adults were asked to make moral judgments with the type of lone potential victim as the between-subject variable. The results generally replicated those of the previous two experiments. Therefore, the present study shows that, in addition to apparent unfairness, latent fairness exists in adults’ relationship-based moral judgments. Moral judgments involving individuals with whom adults have different relationships have different cognitive and affective bases.